Dynamic wireless power transfer system for electric‐powered connected and autonomous vehicle on urban road network. Issue 9 (12th June 2021) - Liu, Qingyun; Hu, Simon; Angeloudis, Panagiotis; Wang, Yibing; Zhang, Lihui; Yang, Qiang; Li, Yongfu
Abstract: This paper investigates the potential impacts of dynamic wireless power transfer (DWPT) systems on the urban road network with a particular focus on charging and energy consumption implications. The paper is motivated by the recent advancement of connected and autonomous vehicle (CAV) technology and innovations on smart transportation infrastructure. An eco‐driving model aiming at energy consumption reduction is developed and a DWPT system layout suitable for charging eco‐driving CAVs at a signalised intersection is proposed. The idea is demonstrated in a simulated environment with different market penetration rate (MPR) of CAVs travelling through a signalized intersection equipped with the proposed DWPT system. The results suggest that as MPR of CAV increases, the energy savings for both CAVs and human‐driven vehicles (HVs) will increase significantly. At full MPR of CAVs, the reduction of average energy consumption of all types of vehicles can reach up to 62%. The average energy transferred and stored per battery electric vehicle can increase by up to 5% and 10%, respectively. These promising results indicate that a well‐designed DWPT system layout together with the eco‐driving behaviour of CAVs can have a positive impact on the urban transportation system in terms of resulting energy consumption and emissions.